ANALISIS KANDUNGAN NUTRISI MIE KERING YANG DISUBTITUSIKAN AMPAS KELAPA - Sylvia Florensy Bawias; Syamsuddin; Prismawiryanti; Ni Ketut Sumarni (KOVALEN: Jurnal Riset Kimia, 2019)
Research has been carried out on the nutritional content of dried noodles substituted with coconut pulp. This study aims to determine the highest total protein content, highest crude fiber content and the highest water content and organoleptic quality of dried noodles substituted with coconut pulp. Dry noodles are made from wheat flour and coconut pulp as the main ingredients. The material ratio is varied to 90:10; 80:20; 70:30 and without the addition of coconut pulp flour. Dry noodles without the addition of coconut pulp flour produced the highest total protein content of 18.57%(b/b) and at the ratio of 70:30 the highest crude fiber was 17.55% (w/w) and the highest water content was 2.63% (w/w). Based on the quality of organoleptic dry noodles the most preferred is at the ratio of 90:10. Keywords: Dry noodles, coconut pulp flour, total protein content, crude fiber content, water content, organoleptic quality